Factors to determine the adoption of online teaching in Tanzania’s universities during the COVID-19 pandemic - Mackfallen, G.Anasel; Swai, L. Idda (PLoS ONE, 2024)
This is an open access article published by PLoS ONE 18(10) October 2023, pg 1-16.